Microfluidic in-line dynamic light scattering with a commercial fibre optic system. - Torquato,LMG; Hélaine,N; Cui,Y; O'Connell,R; Gummel,J; Robles,ESJ; Jacob,D; Cabral,JT (Lab on a Chip: miniaturisation for chemistry, physics, biology, materials science and bioengineering, 2023)
We report the coupling of dynamic light scattering (DLS) in microfluidics, using a contact-free fibre-optic system, enabling the under-flow characterisation of a range of solutions, dispersions, and structured fluids. The system is evaluated and validated with model systems, specifically micellar and (dilute) polymer solutions, and colloidal dispersions of different radii (∼1-100 nm). A systematic method of flow-DLS analysis is examined as a function of flow velocity (0-16 cm s-1), and considerations of the relative contribution of 'transit' and 'Brownian' terms enable the identification of regions where (i) a quiescent approximation suffices, (ii) the flow-DLS framework holds, as well as (iii) where deviations are found, until eventually (iv) the convection dominates. We investigate practically relevant, robust setups, namely that of a capillary connected to microdevice, as well as direct measurement on a glass microdevice, examining the role of capillary dimensions and challenges of optical alignment. We conclude with a demonstration of a continuous flow measurement of a binary surfactant/salt solution, whose micellar dimensions vary with composition, characterised with hundreds of data points (every ∼5 s) and adequate statistics, within a few minutes.